Study to teach : a guide to studying in teacher education - Herne, Steve, 1950-; Jessel, John; Griffiths, Jenny, 1943- (Routledge, 2000)
For all those preparing to teach or involved in further professional development it will provide an essential, accessible and readable companion to their course. Theories of learning are integrated with practical strategies for approaching a topic. Each of the following areas discussed: *active reading and using the library *referencing correctly *making notes and writing clearly *presenting your work orally *developing subject knowledge *using information and communications technology *continuing professional development *developing key relationships *partn.